Anatomical features of the urethra and urinary bladder catheterization in female mice and rats. An essential translational tool - Reis, Leonardo Oliveira; Sopena, Josep Maria Gaya; Fávaro, Wagner José [UNESP]; Martin, Mireia Castilho; Simão, Antônio Felipe Leite; Reis, Rodolfo Borges dos; Andrade, Murilo Ferreira de; Domenech, Josep Domingo; Cardo, Carlos Cordon (FapUNIFESP (SciELO), 2011)
PURPOSE: To present fundamental anatomical aspects and technical skills necessary to urethra and urinary bladder catheterization in female mice and rats. METHODS: Urethral and bladder catheterization has been widely utilized for carcinogenesis and cancer research and still remains very useful in several applications: from toxicological purposes as well as inflammatory and infectious conditions to functional aspects as bladder dynamics and vesicoureteral reflux, among many others. RESULTS: Animal models are in the center of translational research and those involving rodents are the most important nowadays due to several advantages including human reproducibility, easy handling and low cost. CONCLUSIONS: Although technical and anatomical pearls for rodent urethral and bladder access are presented as tackles to the advancement of lower urinary tract preclinical investigation in a broaden sight, restriction to female animals hampers the male microenvironment, demanding future advances.
Características anatômicas da cateterização da uretra e bexiga de camundongos e ratos fêmeas. instrumento essencial na pesquisa pré clínica
Keywords: Anatomy; Rats; Rodent diseases; Urinary tract; animal anatomy; animal experiment; bladder; bladder catheterization; cancer research; carcinogenesis; cost benefit analysis; female; mouse; nonhuman; rat; toxicity testing; urethra; urethral catheterization; vesicoureteral reflux; Animals; Female; Medical Illustration; Mice; Models, Animal; Reproducibility of Results; Sex Factors; Urethra; Urinary Bladder; Urinary Catheterization